2022
DOI: 10.1182/bloodadvances.2021006937
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of SARS-CoV-2 T-cell responses after vaccination in long-term allo-HSCT survivors translates into abated humoral immunity

Abstract: Recipients of allogeneic hematopoietic stem cell transplantation (allo-HSCT) for hematological diseases are at risk of severe disease and death from COVID-19. To determine the safety and immunogenicity of BNT162b2 and mRNA-1273 COVID-19 vaccines, samples from 50 infection-naïve allo-HSCT recipients (median 92 months from transplantation, range 7-340 months) and 39 healthy controls were analyzed for serum IgG against the receptor-binding-domain (RBD) within spike 1 (S1) of SARS-CoV-2 (anti-RBD-S1 IgG) and for S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 22 publications
3
31
0
Order By: Relevance
“… 15 , 24 , 70 Einarsdottir found deficient T-cell responses in patients with low-level serologic response. 13 But Clemenceau et al regularly found T-cell responsiveness in the absence of serologic response. 71 Others have shown that vaccine-induced SARS-Cov-2 S antibody levels in transplant patients and other patients with hematological malignancies are lower than those of healthy volunteers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 15 , 24 , 70 Einarsdottir found deficient T-cell responses in patients with low-level serologic response. 13 But Clemenceau et al regularly found T-cell responsiveness in the absence of serologic response. 71 Others have shown that vaccine-induced SARS-Cov-2 S antibody levels in transplant patients and other patients with hematological malignancies are lower than those of healthy volunteers.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports on covid-19 vaccination in allogeneic transplant recipients have shown encouraging results. 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 But nearly all published data pertain to patients undergoing stem cell transplantation from adult donors. Conditioning regimens or graft versus host disease (GVHD) prophylaxis are usually not detailed.…”
Section: Introductionmentioning
confidence: 99%
“…The results of the antibody ELISA and neutralization assay indicate that, after the third vaccination, antibody concentrations and the distribution of titers remained similar in immunosuppressed individuals, whereas a significant increase was seen in healthy controls. Other studies have also previously shown that the humoral immune response to SARS-CoV-2 vaccination is reduced in 30-60% of HSCT patients [13,14,23]. Currently, there are very few studies on immune responses after third vaccination in HSCT patients.…”
Section: Discussionmentioning
confidence: 99%
“…HSCT was performed at a median of 4.1 years (range 0. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] prior to blood sampling. The subgroup tested prior to the third vaccination contained 10 males and 14 females; the median age was 62 years (range 39-73).…”
Section: Volunteersmentioning
confidence: 99%
“…Recipients of allogeneic haematopoietic stem cell transplantation (allo-HCT) are at elevated risk for severe disease and death from COVID-19 1,2 and mount suboptimal immune responses following COVID-19 vaccination, in particular during the first years after transplantation [3][4][5][6][7] . Previous studies in healthy individuals support an association between adverse reactions after COVID-19 vaccination and induced humoral immunity 8,9 but whether adverse vaccine reactions also are associated with T cell reactivity remains to be elucidated.…”
Section: To the Editormentioning
confidence: 99%